Seasonality, habitat type and locality influenced bird assemblage structure in Nigeria - Muhammad, Sulaiman I.; Ramli, Rosli; Then, Amy Yee Hui (Taylor & Francis, 2018)
This is the first report of the avian assemblage in the study area of Dutse, Nigeria. In addition to recording bird species, the effects of season, dominant vegetation structure, locality and anthropogenic activities on bird abundance, species richness and diversity were investigated. Using the point transect method, 264 points on 48 km of transect were used to count birds between 06:30 and 11:00 from August 2015 to February 2016. A total of 122 bird species of 41 families were recorded. Highest bird species richness was recorded in Warwade, highest abundance in Model, and highest diversity in Malamawa. The dry season and woodland habitat showed higher bird species richness, abundance and diversity than the wet season and shrubland habitat. Tree density was more important in increasing bird abundance than shrub density. Small-scale anthropogenic activities and habitat modification, such as farming, grazing, wood removal and human interference did not appear to have impacted the birds; however, loss of high tree-density woodland habitats may pose a major threat to the bird community in Dutse. The presence of birds of concern in the area suggests the need for conservation efforts of avifauna and as well as the forested habitats in Dutse.